2020
DOI: 10.22541/au.160372859.91708344/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of serum albumin levels with inflammation and clinical outcomes in children with acute bronchiolitis.

Abstract: Objective: To evaluate if hypoalbuminemia on admission predict disease severity in children with acute bronchiolitis (AB). Working hypothesis: Hypoalbuminemia is associated with worse outcome in infants with AB. Study design: Single-centre prospective cohort study. Patient-subject selection : Infants aged <12 month-old with AB. Methodology: Serum albumin levels were determined within the first 24 hours upon inclusion. The primary outcome was the need of pediatric intensive care unit (PICU) admission. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Our results were partially agreed with a study which reported that serum albumin displayed a significant correlation with CRP (r s =-0.27; p =0.008), PCO2 (r s =-0.32; p=0.003), and HCO3 (r=-0.24; p=0.029) levels. However, in contrast to our results they observed that serum albumin level had significant negative correlations with age (r s =0.50; p <0.001) and weight for age percentile (r s =0.33; p= 0.002) (7).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results were partially agreed with a study which reported that serum albumin displayed a significant correlation with CRP (r s =-0.27; p =0.008), PCO2 (r s =-0.32; p=0.003), and HCO3 (r=-0.24; p=0.029) levels. However, in contrast to our results they observed that serum albumin level had significant negative correlations with age (r s =0.50; p <0.001) and weight for age percentile (r s =0.33; p= 0.002) (7).…”
Section: Discussioncontrasting
confidence: 99%
“…The patients with serum albumin <3.5 g/dl presented a five-fold risk of PICU admission (OR 5.5 (CI95% 1-55-19); p =0.008). After adjusting for potential confounders (age, weight for age, presence of comorbidity, BROSJOD score, respiratory acidosis and CRP) in a multivariate logistic regression analysis, serum albumin level less than 3.5 g/dl remained independently with a higher risk of severe AB (a OR 4.1 (1.2-24); p = 0.032) (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations